2020
DOI: 10.3847/1538-4357/ab5f5c
|View full text |Cite
|
Sign up to set email alerts
|

A Catalog of Emission-line Galaxies from the Faint Infrared Grism Survey: Studying Environmental Influence on Star Formation

Abstract: We present a catalog of 208 0.3 < z < 2.1 Emission Line Galaxies (ELG) selected from 1D slitless spectroscopy obtained using Hubble's WFC3 G102 grism, as part of the Faint Infrared Grism Survey (FIGS). We identify ELG candidates by searching for significant peaks in all continuum-subtracted G102 spectra, and, where possible, confirm candidates by identifying consistent emission lines in other available spectra or with published spectroscopic redshifts. We provide derived emission line fluxes and errors, redshi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 110 publications
2
8
0
Order By: Relevance
“…Results tend to agree that higher density environments increase the fraction of quiescent (red) galaxies and we do see this in the COSMOS field (see top right panel of Figure 28; Peng et al 2010;McGee et al 2011;Scoville et al 2013;Darvish et al 2014Darvish et al , 2016. Whether or not the normalization of the MS (defined for starforming galaxies) depends on galaxy environment is still under debate, but many studies identify no variations of MS with environments such as clusters and voids, e.g., Tyler et al (2013), Koyama et al (2014), Ricciardelli et al (2014), Tyler et al (2014), Grossi et al (2018), Paulino-Afonso et al (2019), Pharo et al (2020 (although see Duivenvoorden et al 2016 who found a difference at 1.5 < z < 2 in COSMOS). However, at low redshift (z < 0.3), studies have reported a clear dependence of the MS on galaxy environment (e.g., von der Linden et al 2010, Haines et al 2013, Gu et al 2018, Paccagnella et al 2016).…”
Section: Environmental Trendssupporting
confidence: 73%
“…Results tend to agree that higher density environments increase the fraction of quiescent (red) galaxies and we do see this in the COSMOS field (see top right panel of Figure 28; Peng et al 2010;McGee et al 2011;Scoville et al 2013;Darvish et al 2014Darvish et al , 2016. Whether or not the normalization of the MS (defined for starforming galaxies) depends on galaxy environment is still under debate, but many studies identify no variations of MS with environments such as clusters and voids, e.g., Tyler et al (2013), Koyama et al (2014), Ricciardelli et al (2014), Tyler et al (2014), Grossi et al (2018), Paulino-Afonso et al (2019), Pharo et al (2020 (although see Duivenvoorden et al 2016 who found a difference at 1.5 < z < 2 in COSMOS). However, at low redshift (z < 0.3), studies have reported a clear dependence of the MS on galaxy environment (e.g., von der Linden et al 2010, Haines et al 2013, Gu et al 2018, Paccagnella et al 2016).…”
Section: Environmental Trendssupporting
confidence: 73%
“…Results tend to agree that higher density environments increase the fraction of quiescent (red) galaxies and we do see this in the COSMOS field (see top right panel of Figure 28; Peng et al 2010;McGee et al 2011;Scoville et al 2013;Darvish et al 2014Darvish et al , 2016. Whether or not the normalization of the MS (defined for starforming galaxies) depends on galaxy environment is still under debate, but many studies identify no variations of MS with environments such as clusters and voids, e.g., Tyler et al (2013), Koyama et al (2014), Ricciardelli et al (2014), Tyler et al (2014), Grossi et al (2018), Paulino-Afonso et al ( 2019), Pharo et al (2020) (although see Duivenvoorden et al 2016 who found a difference at 1.5 < z < 2 in COSMOS). However, at low redshift (z < 0.3), studies have reported a clear dependence of the MS on galaxy environment (e.g., von der Linden et al 2010, Haines et al 2013, Gu et al 2018, Paccagnella et al 2016).…”
Section: Environmental Trendssupporting
confidence: 49%
“…The standard deviation of continuum-subtracted fluxes in this surrounding region is combined with the intrinsic flux error of the pixel (largely influenced by the skyline model) to get a flux error estimate, resulting in a continuum-subtracted residual spectrum and an error spectrum. This method of continuum-subtracted peak detection has demonstrated success in detecting emission lines from faint and low-mass sources in other deep surveys (e.g., Yang et al 2017;Pharo et al 2019Pharo et al , 2020. See Figure 2 for some example spectra showing the continuum subtraction.…”
Section: Redshift Fittingmentioning
confidence: 99%
“…For example, Guo et al (2016b) measured star formation burstiness with Keck/DEIMOS spectroscopy at 0.5 < z < 1 for 164 galaxies with ( )  < <  M M 8.5 log 10.5, but only 17 galaxies in the sample had ( )  <  M M log 9. Grism spectroscopy can be a means to achieve the necessary depth; Pharo et al (2020) measured emission lines for ∼50 low-mass galaxies at 0.3 < z < 2 with Hubble Space Telescope (HST) WFC3-G102 near-IR grism spectroscopy with a 40-orbit depth (FIGS;…”
Section: Introductionmentioning
confidence: 99%